Farming Bivalves Under Climate Change: The Effects of Marine Heatwaves and Invasive Tunicates on Mussel (Mytilus edulis) Aquaculture - Shelby B. Clarke; Jasmine Talevi; Luc A. Comeau; André Nadeau; John Davidson; Ramón Filgueira (Journal of Marine Science and Engineering, 2026)
Marine heatwaves and invasive tunicate fouling increasingly co-occur in mussel aquaculture, yet their combined effects on rope-level performance and plankton dynamics remain unclear. A 9-day field-based mesocosm experiment in Georgetown Harbour (Prince Edward Island, Canada) examined the independent and interactive effects of heatwaves (~4.5 °C above ambient) and tunicates on 50 cm sections of Mytilus edulis culture rope. Oxygen consumption rate (OCR), clearance rate (CR), capture efficiency (CE), absorption efficiency (AE), scope for growth (SFG), and condition index (CI) were quantified to assess rope-level performance, and net primary productivity (NPP) was examined to evaluate ecosystem-level effects. OCR increased with rope biomass and exhibited a biomass-temperature interaction, with a stronger increase observed under heatwave conditions. CR also increased with biomass and decreased with temperature. These shifts in metabolism and feeding resulted in near-zero SFG and reduced CI under heatwave conditions, independent of biomass. Both grazer biomass and temperature significantly influenced NPP under high-light conditions, with increasing biomass reducing NPP. Tunicate presence enhanced the retention of smaller particles, highlighting species-specific differences in particle retention within the mussel rope community. The findings suggest that warming can reduce the performance of mussel rope communities, while fouling-associated shifts in community composition may amplify grazing pressure and alter particle removal dynamics, with potential consequences for ecosystem functioning.

Physiology and behaviour of eastern oysters (Crassostrea virginica) and soft-shell clams (Mya arenaria) under hypoxic and heatwave conditions - Jasmine Talevi; Shelby B. Clarke; Michael R.S. Coffin; Luc A. Comeau; Ramón Filgueira (Marine Environmental Research, 2026)

Metabolic depression explains differences in vulnerability to low oxygen between two species of temperate marine bivalves - Keryn Winterburn; Jasmine Talevi; Shelby B. Clarke; Jeff C. Clements; Michael R.S. Coffin; Ramón Filgueira (Marine Environmental Research, 2025)